2002
DOI: 10.1111/j.2042-3306.2002.tb05417.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribose supplementation in maximally exercising Thoroughbreds

Abstract: A diverse group of studies, which are equine exclusive, indicate that ribose administered to myocardial and skeletal muscle tissue stimulates ATP production and recovery. This study investigated the effects of ribose supplementation on blood and muscle metabolites and performance in Thoroughbred geldings performing a maximal treadmill standardised exercise test (SET). In Experiment 1, 6 conditioned Thoroughbred geldings performed a baseline SET and horses were assigned to one of 2 experimental treatment groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…GPLC transports fatty acids to the mitochondria for oxidation, CoQ10 is essential for adenosine-5 0 -triphosphate (ATP) production as a cofactor in the mitochondrial electron transport chain, and D-ribose is an intergral structural component of ATP. These three nutrients have been demonstrated to increase exercise capacity in humans [100][101][102][103] and equids [58,104], presumably by stimulating ATP production and recovery while supporting ATP energy substrates at the same time [105]. Daily ribose supplementation (0.07 g/kg BW, twice daily) for 14 days in the diet of exercising geldings resulted in lower blood ammonia-N and plasma lactic acid during recovery after a standardized exercise test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GPLC transports fatty acids to the mitochondria for oxidation, CoQ10 is essential for adenosine-5 0 -triphosphate (ATP) production as a cofactor in the mitochondrial electron transport chain, and D-ribose is an intergral structural component of ATP. These three nutrients have been demonstrated to increase exercise capacity in humans [100][101][102][103] and equids [58,104], presumably by stimulating ATP production and recovery while supporting ATP energy substrates at the same time [105]. Daily ribose supplementation (0.07 g/kg BW, twice daily) for 14 days in the diet of exercising geldings resulted in lower blood ammonia-N and plasma lactic acid during recovery after a standardized exercise test.…”
Section: Discussionmentioning
confidence: 99%
“…Various dietary supplements have been proposed to alleviate exercise-related injuries and illnesses [40][41][42][43][44][45][46][47][48][49][50]. Although many of these same compounds have been used in horses [37,[48][49][50][51][52][53][54][55][56][57][58], their effect on exercise-induced proinflammatory responses has not been investigated in detail [55]. Here, we have examined the effect of a nutritional supplement on the proinflammatory response to exercise in 2-year-old Thoroughbred racehorses in training.…”
Section: Introductionmentioning
confidence: 94%
“…It has been suggested that supplemental ribose may aid in muscle recovery by maintaining or increasing ATP resynthesis rates after bouts of strenuous exercise (1,5,16,18,22,27,28,35). Previous studies (4,17,20), however, have reported no energy-related or performance-related benefits to ribose supplementation during exercise.…”
Section: Discussionmentioning
confidence: 92%
“…Based on the previous literature indicating that the addition of protein (1,3,15,25,30,33) may improve glycogen resynthesis and ribose (1,5,16,18,22,27,28,35) may preserve and increase the capacity for energy transfer during exercise, we hypothesized that the carbohydrate-, ribose-, and protein-containing repletion drink would augment the chronic endurance training-induced improvements in aerobic capacity and endurance performance after an 8-week period of endurance training and supplementation. Furthermore, we hypothesized that the inclusion of protein in the experimental formula may increase fat-free mass (FFM) more than carbohydrates alone (14) in cyclists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation